Conceptual review and teaching experiences on the use of active-participatory methodologies for critical thinking development in Higher Education - González-Fernández, Natalia (2025)
This study analyses the actual status in the national (Spain) and international literature about “Active and Participative Methods” (MAP), and “Critical Thinking” (PC) development, two fundamental concepts on Higher Education (ES). Furthermore, a systematic review of the recent national experiences that focus on the impact of MAP in PC development in ES is carried out. This paper emerges as a consequence of the actual lack of consensus about the conceptualization of these terms, due to the dispersion of the information available in the literature, and due to the lack of agreement amongst the authors about MAP influence in PC development. A bibliographic search in 2 national and 4 international databases was carried out. The paper selection criteria were based on the paper contribution to a system of categories and subcategoriesspecifically designed for the revision. Revision results allowed to construct a one-paper compilation of the basic aspects and characteristics of MAP, and PC, while simultaneously reviewing the latest national publications that analyze the relationships between both concepts.